Low back pain beliefs are associated to age, location of work, education and pain-related disability in Chinese healthcare, professionals working in China: a cross sectinal survey - Tan, Boon-Kiang; Smith, Anne; O'Sullivan, Peter; Chen, G.; Burnett, A.; Briggs, Andrew (Biomed Central Ltd, 2014)
Background: Low back pain (LBP) is the leading cause of disability worldwide. Evidence pointing towards a more efficacious model of care using a biopsychosocial approach for LBP management highlights the need to understand the pain-related beliefs of patients and those who treat them. The beliefs held by healthcare professionals (HCPs) are known to influence the treatment advice given to patients and consequently management outcomes. Back pain beliefs are known to be influenced by factors such as culture, education, health literacy, place of work, personal experience of LBP and the sequelae of LBP such as disability. There is currently a knowledge gap among these relationships in non-western countries. The aim of this study was to examine the associations between LBP-related beliefs among Chinese HCPs and characteristics of these HCPs. Methods: A convenience sample of 432 HCPs working in various health settings in Shanghai, China, completed a series of questionnaires assessing their demographic characteristics, LBP status, pain-related disability and their beliefs about their own LBP experience, using the Back beliefs Questionnaire (BBQ) and the Fear Avoidance Beliefs Questionnaire (FABQ).Results: Younger Chinese HCPs (20–29 years) held more negative beliefs and attitudes related to LBP compared to older HCPs (>40years; BBQ mean difference [95% CI]: 2.4 [0.9 - 3.9], p = 0.001). HCPs working outside tertiary hospitals had poorer beliefs concerning the inevitable consequences of LBP (BBQ mean difference [95% CI]: -2.4 [-3.8 - -1.0], p = 0.001). HCPs who experienced LBP had higher level of fear avoidance beliefs when experiencing high LBP-related disability (FABQ-physical mean difference [95% CI]: 2.8 [1.5 - 4.1], p < 0.001; FABQ-work mean difference [95% CI]: 6.2 [4.0 - 8.4], p < 0.001)) and had lower level of fear avoidance beliefs if they had completed postgraduate study(FABQ-physical mean difference [95% CI]: 2.9 [-5.8 - 0.0], p = 0.049).Conclusion: This study suggests that LBP-related beliefs and attitudes among Chinese HCPs are influenced by age, location of work, level of LBP-related disability and education level. Understanding back pain beliefs of Chinese HCPs forms an important foundation for future studies into the condition and its management in China.